The Influence Of Work Discipline And Quality Of Worklife On The Performance Of Employees Of The Ministry Of Religious Affairs Office Of Tasikmalaya Regency - Renita Hera Nurul Aulia; Kusuma Agdhi Rahwana; Arga Sutrisna (Journal of Indonesian Management, 2022)
This study aims to find out how much influence Work Discipline and Quality Of Work Life have on Employee Performance at the Tasikmalaya Regency Ministry of Religious Affairs Office. The method used in this study is quantitative with a survey approach. With a research sample of 41 people as respondents to the Tasikmalaya Regency Ministry of Religious Affairs Office based on 41 known population data. The data used is using primary data. The analysis tool used in this study is multiple linear regression using the SPSS support application version. Based on data that have met the validity test, reliability tests and classical assumption tests are processed so as to produce regression equations as follows: Y = 73,820 + 0.388 X_1 + 0.392 X_2. The test results showed that partially showing the variables used in the study, namely work discipline and quality of work life, had a significant effect on the performance of employees at the Tasikmalaya Regency Ministry of Religious Affairs Office. Simultaneously there is a positive and significant influence of work discipline and quality of work life together on employee performance based on the testing of multiple linear regression analysis obtained fghitung of 73,820 signatures of 0.001. With the Determination Coefficient test, it gets an R Square value of 0.398 or 39.80%. It shows the influence of Work Discipline and Quality Of Work Life on Employee Performance and 60.20% is the influence of other variables beyond the variables used in this study.